Effect of Arm Pivot Joints on Stiffness Discrimination in Haptic Environments - Khandaker Nusaiba Hafiz; Ernur Karadoğan (Multimodal Technologies and Interaction, 2022)
We investigated the effect of arm pivot joints that are typically used during haptic exploration by evaluating four joints of the human arm (metacarpophalangeal joint of the index finger, wrist, elbow, and shoulder joints). Using a virtual stiffness discrimination task, a four-session psychophysical experiment was conducted with 38 participants (25 male and 13 female); each session was conducted with one of the four joints as the pivot joint during haptic exploration. The participants were asked to judge the stiffness of the top surface of two computer-generated cylinders by determining the stiffer one while using their dominant hand’s index finger. A two-alternative forced-choice procedure was employed by assigning one cylinder a constant stiffness value of 1.0 N/mm (standard side) and the remaining cylinder a variable stiffness value (comparison side). Using a custom-made stylus for the Geomagic TouchTM (3D Systems, Inc., Rock Hill, SC, USA) haptic interface, the participants were able to feel the stiffness of these virtual surfaces only with their index fingers. It was observed that the average Weber fraction monotonically decreased as the pivot joint shifted toward the torso (i.e., a shift from the metacarpophalangeal joint to the shoulder joint); this decrease was not statistically significant, which suggests that the selection of the pivot joint was not a determining factor for the sensitivity to discriminate stiffness. In general, the palpation speed and force exerted by the participants on the standard side during the haptic exploration showed a tendency to increase when the pivot joint shifted toward the torso; the difference in average palpation speed and force across the pivot joints was not statistically significant.